Information communication technology, village development and security committee and village vision movement: a recipe for rural success in Malaysia - Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva; Abu Hassan, Musa (Canadian Center of Science and Education, 2010)
The growing body of literature associated with information and communication technology within the rural community had examined numerous factors and interrelationships in order to gain a better understanding on the usage of computers among rural people. Rural administrators play a vital role to ensure information and communication technology is utilized regularly by the rural society. Thus it is significant to draw to attention to the factors affecting rural administrators’ information and communication technology usage and its implications to rural administrators professional development strategies. This article would be of great help for future researchers who are searching for the path to further explain the determinants of information and communication technology acceptance and its utilization based on various models depicted in the literature.